Survival and factors predictive of survival in patients with thymic carcinoma - Suparauk Geanphun (2020)
© 2019, Faculty of Medicine Siriraj Hospital, Mahidol University. Objective: Thymic carcinoma is a rare malignancy that has a poor prognosis and low 5-year survival. The rarity of this disease and the variety of histologic subtypes has limited the evidence needed to establish disease-specific staging and treatment guidelines. The aim of this study was to investigate overall survival, the factors that predict survival, and the treatment modalities that influence survival in patients with thymic carcinoma. Methods: All thymic carcinoma cases diagnosed and treated at Siriraj Hospital (Bangkok, Thailand) during 1997-2013 were retrospectively reviewed. Univariate and multivariate analyses were performed to identify factors that predict survival, and overall survival was estimated by Kaplan-Meier method. Results: Of the 45 patients diagnosed during the study period, 8 were lost to follow-up. The remaining 37 patients were included in our analysis. The median survival time was 2.5 years, with 5-year and 10-year survival of 40% and 16%, respectively. In univariate analysis, tumors >10 cm (p=0.017), high-grade histologic subtypes (p=0.014), and high Masaoka stage (p=0.011) were significant determinants of survival. Multivariate analysis revealed tumor size (HR: 3.594, 95% CI: 1.103-11.714; p=0.034) and high-grade histologic subtypes (HR: 8.175, 95% CI: 1.689-39.566; p=0.009) to be independent predictors of survival. Patients who underwent tumor removal had significantly longer median survival time than those who didn't (3.85 vs. 0.63 years; p=0.005). Conclusion: Thymic carcinoma patients have low 5-year and 10-year survival. Tumor size and high-grade histologic subtype were identified as independent predictors of survival, and surgical therapy was found to be significantly associated with longer median survival time.